Using GPS near the forest and quality control - Pirti, A (TAYLOR & FRANCIS LTD, 2005)
This paper attempts to provide some insights into the fading properties of GPS signals. When a GPS signal reaches the antenna, it suffers from masking and blocking effects from surrounding objects. With respect to these effects, GPS signals can he divided into clear signals, shadowed signals, and blocked signals. In this article we shall examine the performance and use of GPS based data acquisition systems near forest. As a general rule, a clear view of the sky is preferred when using GPS for determining location. This means that using GPS near forest is one of the most demanding uses of technology and one that requires particular attention when evaluating GPS receivers that will be used in such an environment. The signal transmitted by GPS satellites are extremely, low power, and the GPS signal is about 100 times weaker than the general background radiation at that frequency. The signal passing through your body right now from a local television or radio station is almost certainly several thousand times stronger than a GPS signal. GPS receivers use sophisticated signal processing techniques to lock onto and track the GPS satellites. However, the relatively low power of these signals can indeed pose problems when the signal is further degraded by a forest canopy. Humidity of the leaves and the forest is the critical factor for GPS performance near the forest area. Water laden leaves of tree attenuate more signal than those that are thy. GPS signals will be present with weak signal strengths and positions that are computed from weak signals tend to be less accurate. This paper evaluates GPS positional accuracy, precision and performance near forest areas. As a result of this attenuation, positions are computed from weak signals and tend to be less accurate.
Keywords: Engineering; Geology; Remote Sensing